Problem-solving Strategy: Mathematical Problem-solving Model Within the Polya' Framework - Nico Pradana, Lingga (KnE Social Sciences, 2024)
Mathematical problem-solving is very important for students to learn and understand, which can later be used in solving problems that exist in everyday life. This study aims to analyze the mathematical problem-solving model within the framework of Polya’ theory. The subjects in this study were fifth grade students showing their strategy to solve mathematical problem. We analyzed the student’ problem-solving strategy with real word problems and configured their solution. The results of this study are in the problem-solving process, the subject has completed according to the stages of Polya. At each step, the indicators work together in a unique way to solve a math problem. This research initiates that the connection between indicators in problem-solving can form a cycle of resolution. Keywords: problem solving, mathematical problems, mathematics ability